Designing for privacy from Islamic perspectives using value sensitive design - Ahmadon, Fadzlin; Nordin, Rosmawati; Md Rawi, Rashidah (2012)
One of the advantages of computerized record-keeping system is its ability to shield sensitive information from prying eyes. There are many system development methodologies to safeguard privacy and Value Sensitive Design is one approach that focuses on embedding moral values into technology design.Islamic traditions while supporting commonly regarded moral values such as justice and truth often has additional requirements for believers to fully uphold those values from Islamic perspective. Privacy is one such value.While in agreement on many techniques introduced by western scholars to safeguard privacy in system design, the unique concept of awrah as part of privacy consideration in Islam is one such additional reflection for system designers.